RBM5/LUCA-15 — Tumour Suppression by Control of Apoptosis and the Cell Cycle? - Mirna Mourtada-Maarabouni; Gwyn T. Williams (The Scientific World Journal)
The candidate tumour suppressor gene, LUCA-15, maps to the lung cancer tumour suppressor locus 3p21.3. The LUCA-15 gene locus encodes at least four alternatively spliced transcripts, which have been shown to function as regulators of apoptosis, a fact that may have a major significance in tumour regulation. This review highlights evidence that implicates the LUCA-15 locus in the control of apoptosis and cell proliferation, and reports observations that significantly strengthen the case for tumour suppressor activity by this gene.